Treatment of tympanic membrane perforation with topical epidermal growth factor: progress towards clinical application - Nayak, Puneeth S.; Harugop, Anil S.; Patil, Prashant H.; T. V. R. K., Prasad; Goswami, Lakshmi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Chronic otitis media is a widespread disease of developing countries, especially of the lower socio-economic group. Medical cost in hospitals associated with tympanoplasty for treating CSOM is very high. Our study investigates the efficacy of epidermal growth factor along with chemical cautery in healing of chronic tympanic membrane perforation on an outpatient department (OPD) basis. Hence providing a cheaper and cost effective treatment alternative to the patients. Methods: A total number of 70 patients with signs of COM attending ENT OPD were selected. The patients were randomly assigned into 2 groups each with a sample size of 35. Otoendoscopy and pure tone audiometry was performed. Group A was treated with EGF with chemical cautery and group B was treated with only chemical cautery. Both groups were followed up after 15 days, one month and second month of the procedure in ENT outpatient clinic. Results: The success rate of these non-healing perforation was found to be significantly higher in group A (29 [82.86%]) compared with group B (17 [65.71%]) with P value of 0.0070*. Conclusions: This study shows a statistically significant result with topical application of epidermal growth factor in small to medium non-healing central tympanic membrane perforation. Due to the promising result of epidermal growth factor, it could be considered as office myringoplasty.